A Scoping Study on the Ethics of Health Systems Research. Issue 3 (1st April 2016) - Bachani, Abdulgafoor M.; Rattani, Abbas; Hyder, Adnan A.
Abstract: Currently, health systems research (HSR) is reviewed by the same ethical standards as clinical research, which has recently been argued in the literature to be an inappropriate standard of evaluation. The issues unique to HSR warrant a different review by research ethics committees (RECs), as it does not impose the same risks to study participants as other types of clinical or public health research. However, there are limited tools and supporting documents that clarify the ethical considerations. Therefore, there is a need for additional reflection around ethical review of HSR and their consideration by RECs. The purpose of this paper is to review, understand, and synthesize the current state of literature and practice to inform these deliberations and the larger discourse on ethics review guidelines for HSR. This paper presents a review of the literature on ethics of HSR in the biomedical, public health, and implementation research to identify ethical considerations specific to HSR; and to identify examples of commonly available guidance and/or tools for the ethical review of HSR studies. Fifteen articles were identified on HSR ethics issues, and forty‐two international academic institutions were contacted (of the responses (n=29), no institution had special ethical guidelines for reviewing HSR) about their HSR ethics review guidelines. There appears to be a clear gap in the current health research ethics discourse around health systems research ethics. This review serves as a first step (to better understand the current status) towards a larger dialogue on the topic.